STUDI SOSIAL EKONOMI PENGGUNAAN LABAN HUTAN KONVERSI UNTUK TRANSMIGRASI DI KALIMANTAN SELATAN - Ismatul Hakim (Jurnal Penelitian Hasil Hutan, 1991)
The transfer  of  convertion  forest  lands  into  transmigration  areas must   be geared  towards   improving   and  developing  land productivity  in  order  to  obtain  optimun  socio-economic   role  of the  rasources   for  the transmigrant  and  sustainability of  agricultural  production.  In  this rasearch   respondent  samples  are purposively   taken from  the villages  of  Ambawang  (15 families)  as  a less   successful transmigration  area and of  Domit  (115  familia)  as a successful  area.  Both  are located  in Jorong  sub-district,  Tanah  laut District,  South  Kalimantan.The  resulis showed thet the  per capita  income  of  respondent  family   in Damit  village is higher   than  that in Ambawang    village  (almost twice)  and  land productivity in Damit  village is even  3 limes as in  much  as in .Ambawang  village   These mean  that transmigration  program  in Damit village is more  succasful   than  in Ambawang village.  Land  utilization  in  Damit  and   Ambowang  villages is as foUows  : I t e ms                                             Precentage of  land  us   Damit      Ambawang.Rice field                                              181,80   125,71Home  garden                                   104,17   82,76Farm land                                            26,57     34,57This  can  be interpreled   that more  land  in Damit  is suitable  for  rice field.   Land  use in transmigration   areas  depends  on  the suitability level of land for  agricultaral  extensification,  the availability  of  water for  irrigation,  and background  experience  background   of  transmigration family.An  average  number   of  mandays  per family  per year  is 2140.49 mandays   which  consists   of:  farming,  rice field  woking,  off- farming and  home gardening  are 36.77%, 24.16%, 21.52%,  and  16.60%, respectively.  The total income  per family  both  villages is Rp  1,275,086.300The saving  level per  family  in Domit  is  Rp 333,794.20 and in  Ambowang  is Rp   541,303.00  but the Gross   Domestic  Product  (PlJB)  in Damit is Rp 873,075.00 and  PDB  in Ambawang  is Rp  265,431.50. These   mean  that  the  equalization   level of  income  distribution  and  the occess  of transmigration  community   to the village development   are better in  Damit  than  on .Ambawang.In general,  it can  be concluded   that practicing  transmigration  program   by  using  convertion  forest   land  in   Jorong,  South   Kalima.tan can  improve  land  productivity   and  socio-economic   status  of  the tronsmigrants  which  makes  them  enjoying  beller  life in the  new areas.  The in depth  study  on  socio-economic    aspeci  of  transmigration   is required  by  comparing   their  socio-economic   status  in their  new   area  to their  previous  ones   in Java.